2000
DOI: 10.1021/bi992821q
|View full text |Cite
|
Sign up to set email alerts
|

The X6 “Thermostabilizing” Domains of Xylanases Are Carbohydrate-Binding Modules:  Structure and Biochemistry of the Clostridium thermocellum X6b Domain,

Abstract: Many polysaccharide-degrading enzymes display a modular structure in which a catalytic module is attached to one or more noncatalytic modules. Several xylanases contain a module of previously unknown function (termed "X6" modules) that had been implicated in thermostability. We have investigated the properties of two such "thermostabilizing" modules, X6a and X6b from the Clostridium thermocellumxylanase Xyn10B. These modules, expressed either as discrete entities or as their natural fusions with the catalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
177
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(192 citation statements)
references
References 56 publications
12
177
1
2
Order By: Relevance
“…8 and Table III). The ⌬H and T⌬S values for the binding of the CBM35 to oat-spelt xylan are negative, similar to Man5C-CBM35 and other CBMs that interact with soluble polysaccharides (10,11,15). Titration of the apo form of Abf62A-CBM35 with calcium demonstrates that the protein binds tightly to the divalent metal ion (Fig.…”
Section: Identification Of the Cbm35 Family Of Protein Modules-mentioning
confidence: 60%
See 2 more Smart Citations
“…8 and Table III). The ⌬H and T⌬S values for the binding of the CBM35 to oat-spelt xylan are negative, similar to Man5C-CBM35 and other CBMs that interact with soluble polysaccharides (10,11,15). Titration of the apo form of Abf62A-CBM35 with calcium demonstrates that the protein binds tightly to the divalent metal ion (Fig.…”
Section: Identification Of the Cbm35 Family Of Protein Modules-mentioning
confidence: 60%
“…Previous studies have shown that CBMs from families 4, 6, 9, and 22 contain one or more calcium ions located at sites remote from the ligand binding cleft, suggesting a structural role for the metal (10,29,(33)(34)(35). In support of this view, removal of calcium from both cellulose and xylan-binding CBM4s reduced the temperature at which the proteins unfolded by 8°C (34) and 23°C (35), respectively.…”
Section: Identification Of the Cbm35 Family Of Protein Modules-mentioning
confidence: 71%
See 1 more Smart Citation
“…increasing the concentration of the enzyme on the surface of the substrate) leads to more rapid degradation of the polysaccharide [22]. There are numerous examples in the literature where proteolytic excision or genetic truncation of CBMs from the catalytic modules results in significant decreases in the activity of the enzymes on insoluble, but not soluble polysaccharides (see [2,[22][23][24][25][26][27][28][29] for examples). It should be pointed out that there are examples of CBMs that have become components of the substrate-binding sites of glycoside hydrolases, and are pivotal to the substrate specificity and mode of action of the cognate enzymes.…”
Section: Cbm Binding and Polysaccharide Hydrolysismentioning
confidence: 99%
“…Ligand recognition by these CBMs is driven primarily through an increase in entropy, resulting in the desolvation of the interacting macromolecules (Creagh et al, 1996). By contrast, enthalpy drives the binding of CBMs to discreet polysaccharide chains, where both polar and apolar interactions occur, while entropy has a negative impact on overall affinity (Charnock et al, 2000(Charnock et al, , 2002aBolam et al, 2001;Boraston et al, 2002aBoraston et al, , 2002b. The negative entropy may reflect conformational restriction of the ligand bound to the protein, which is not entirely offset by the release of tightly bound water molecules (for review, see Boraston et al, 2004).…”
Section: Crystalline Cellulose Recognitionmentioning
confidence: 99%